Chronic treatment with corticosterone increases the number of tyrosine hydroxylase-expressing cells within specific nuclei of the brainstem reticular formation - Busceti, Carla Letizia; Bucci, Domenico; Scioli, Mariarosaria; Di Pietro, Paola; Nicoletti, Ferdinando; Puglisi-Allegra, Stefano; Ferrucci, Michela; Fornai, Francesco (Frontiers in Neuroanatomy, 2022)
Cushing's syndrome is due to increased glucocorticoid levels in the body, and it is characterized by several clinical alterations which concern both vegetative and behavioral functions. The anatomical correlates of these effects remain largely unknown. Apart from peripheral effects induced by corticosteroids as counter-insular hormones, only a few reports are available concerning the neurobiology of glucocorticoid-induced vegetative and behavioral alterations. In the present study, C57 Black mice were administered daily a chronic treatment with corticosterone in drinking water. This treatment produces a significant and selective increase of TH-positive neurons within two nuclei placed in the lateral column of the brainstem reticular formation. These alterations significantly correlate with selective domains of Cushing's syndrome. Specifically, the increase of TH neurons within area postrema significantly correlates with the development of glucose intolerance, which is in line with the selective control by area postrema of vagal neurons innervating the pancreas. The other nucleus corresponds to the retrorubral field, which is involved in the behavioral activity. In detail, the retrorubral field is likely to modulate anxiety and mood disorders, which frequently occur following chronic exposure to glucocorticoids. To our knowledge, this is the first study that provides the neuroanatomical basis underlying specific symptoms occurring in Cushing's syndrome.